Analysis of Propeller Selection for Unmanned Aircraft - Kusumoaji, Danartomo; Aziz, Abdul; Rismayanti, Irma; Nahak, Ildefonsa A. F. (Jurnal ILMU DASAR, 2024)
Unmanned aircraft are usually used to perform missions, for example surveillance missions. This mission is not always carried out in a suitable location. Researchers must ensure that the aircraft can take off properly. For this reason, runway distance greatly affects the performance of the aircraft. The aircraft can fail to take off due to the lack of thrust generated by the propeller. The propeller diameter size of each unmanned aircraft can differ from one another and this difference in propeller diameter causes a difference in thrust force. Therefore, it is very important to determine the right propeller diameter to be used on an unmanned aircraft that is adjusted to the runway distance. This propeller selection analysis is carried out using experimental methods, which is tool testing and simulation with Propeller Power Calculator software. The results of this study can be seen that a propeller with a larger diameter will produce a greater thrust force. The size of the diameter and pitch and the number of blades of a propeller can also affect the amount of thrust generated. This will be a consideration for choosing a propeller to be used on an unmanned aircraft. So that the selected propeller can be used optimally by reviewing the amount of thrust that is influenced by the amount of diameter.